Catalytic Production of Bio-Diesel from Algal Oil - Rajeshwer Rao, Y.; Deshmukh, S.S. (Asian Journal of Chemistry, 2010)
Bio-diesel derived from oils and fats by transesterification with alcohols is a renewable, biodegradable and non-toxic fuel for compression ignition engine. As an alternate fuel bio-diesel has attracted considerable attention during the past decades. Commercial production of bio-diesel from vegetable oils is not economically viable and use of unconventional microbial sources particularly micro-algae for the production of bio-diesel is of practical significance. The present work describes conver-sion of algal oil to bio-diesel by transesterfication with methanol in the presence of metal ion catalysts. The bio-diesel obtained was analyzed for methyl ester components and fuel related physical properties as per ASTM methods.